Eccrine sweat glands associate with the human hair follicle within a defined compartment of dermal white adipose tissue. (1st May 2018) - Poblet, E.; Jimenez, F.; Escario‐Travesedo, E.; Hardman, J.A.; Hernández‐Hernández, I.; Agudo‐Mena, J.L.; Cabrera‐Galvan, J.J.; Nicu, C.; Paus, R.
Summary: Background: Eccrine sweat glands (ESGs) are critical for thermoregulation and are involved in wound healing. ESGs have traditionally been considered as separate skin appendages without connection to the pilosebaceous unit (PSU). However, recent preliminary evidence has encouraged the hypothesis that the PSU and ESG are more interconnected than previously thought. Objectives: To re‐evaluate the morphology of human skin adnexa with an integrated three‐dimensional (3D) perspective in order to explore the possible interconnections that the PSU and the ESG may form. Methods: A systematic 3D reconstruction method of skin sections, direct visualization of human scalp follicular unit transplant grafts and a scalp strip ex vivo were used to validate and further explore the hypothesis. Results: We demonstrate that the coiled portion of most ESGs is morphologically integrated into the PSU of human scalp skin and forms a structural unit that is embedded into a specific, hair follicle‐associated region of dermal white adipose tissue (dWAT). This newly recognized unit is easily accessible and experimentally tractable by organ culture of follicular units and can be visualized intravitally. Conclusions: We propose a model of functional human skin anatomy in which ESGs are closely associated with the PSU and the dWAT to form a common homeostatic tissue environment, which may best be encapsulated in the term 'adnexal skin unit'. The challenge now is to dissect how each component of this superstructure of human skin functionally cooperates with and influences the other under physiological conditions, during regeneration and repair and in selected skin diseases.